Assessing firefighters’ tourniquet skill attainment and retention – A controlled simulation-based experiment - Dragset, Erik; Blix, Sigurd Wisborg (UiT Norges arktiske universitet, 2019)
Background: The aim of this study was to train and assess firefighters’ skill attainment in the use of tourniquets, and to assess their skill retention after three months. The purpose is to show whether firefighters can successfully apply a tourniquet after a short course based on the new national recommendation for civilian prehospital tourniquet use. Material and methods: This was a prospective experimental study. The study population was firefighters in Oslo and Tromsø, and the inclusion criterion was any on-duty firefighter. The first phase consisted of baseline pre-course testing, a short tourniquet course based on the new national tourniquet recommendation, followed by immediate retesting. The second phase consisted of retesting of skill retention after 3 months. Primary outcome was absent distal pulse (confirmed with doppler ultrasound), correct placement (i.e. 5-10cm proximal to wound) and application time. Results: There were 109 participants pre-course (T1), 105 immediately after the course (T2) and 62 participants at the three-months re-test (T3). The firefighters achieved a significantly greater proportion of successful tourniquet applications immediately after the course (91.4%, 96 of 105) as well as three months later (87.1%, 54 of 62) compared to 50.5% (55 of 109) pre-course (p=0.009). Mean application time was 59.6s (55.1-64.2) in T1, 34.9s (33.3-36.6) in T2 and 37.7s (33.9-41.4) in T3. The firefighters were significantly slower pre-course compared to both T2 (mean difference 24.7s, p<0.000) and T3 (mean difference 22.0s, p<0.000), but not between T2 and T3 (mean difference 2.7s, p=0.983). Conclusion: Firefighters are able to successfully apply a tourniquet after a 45-minute course based on the new recommendation for civilian prehospital tourniquet use. Skill retention after three months was satisfactory for both successful application and application time. We strongly recommend that tourniquets should be a part of firefighters’ hemorrhage control kit, but they should not be implemented ...